Women’s Preferences for Body Image Programming: A Qualitative Study to Inform Future Programs Targeting Women Diagnosed With Breast Cancer - Brunet, Jennifer; Price, Jenson; Harris, Cheryl (Frontiers in Psychology, 2021)
Purpose: This paper describes women’s opinions of the attributes of the ideal body image program to inform the design, development, and implementation of future programs for those diagnosed with breast cancer. Methods: Deductive-inductive content analysis of semi-structured interviews with 26 women diagnosed with breast cancer (mean age=55.96 years; mean time since diagnosis=2.79 years) was performed. Findings: Participants’ opinions regarding the ideal body image program are summarized into five themes, mapping the where (community-based, hospital-based, or online), when (across the cancer continuum or at specific points), how (peer-led programs, professional help, events, presentations/workshops, resources, support groups), what (self-care, counselling and education for self, education for others, support for addressing sexuality/sexual health concerns, and concealing treatment-related changes), and who (team approach or delivered by women, health professionals, make-up artists). Conclusions: This study provides useful data on what women believe are the attributes of the ideal body image program, which can contribute to efforts aimed at developing and delivering body image programs for women diagnosed with breast cancer that prioritize their needs and requirements.